Auditory Brainstem Response profile in speech delay patients at Universitas Gadjah Mada Academic Hospital - Mahatma Sotya Bawono; Ade Febrina Lestari; Widiarahma Hapsari; Herfis Avidati; Shinta Kusumalarna Sari (PERHATI-KL, 2021)
ABSTRACTBackground: Speech delay is one of the most common causes of developmental disorders in children and the reason for patients to be referred to the Electromedical Unit. Purpose: To find out the profile of Auditory Brainstem Response (ABR) results in pediatric patients with speech delays at the Electromedical Clinic of UGM Academic Hospital. Method: This was a retrospective descriptive observational study using secondary data, using total sampling method from January 1 to December 31, 2019. The respondents were 86 children who met the inclusion and exclusion criteria. Most of the respondents were male (68.6 %) in the age range of 2-<3 years (45.3%). Result: ABR examination found 68 children (79.1%) classified as normal ABR and 18 children (31.4%) with abnormal ABR. The highest number of respondents who obtained normal ABR results were male (42.6%), while abnormal ABR results were higher in female (66.7%). Respondents with normal and abnormal ABR results were mostly in the age range of 2-<3 years, consisted of 29 children (42.6%) and 10 children (55.5%) respectively. The respondents in this study were mainly categorized in the range of severe hearing loss (66.6%). Most of the respondents (77.8%) belong to the type of sensorineural hearing loss (SNHL). Conclusion: Respondents with abnormal ABR results showed predominantly (83.3%) had a hearing loss on both sides of the ear (bilateral). Pediatric patients with speech delay who underwent ABR testing mostly showed normal hearing. The majority of them were male, between 2-3 years of age.Keywords: ABR (Auditory Brainstem Response), hearing loss, hearing test, speech delayABSTRAKLatar belakang: Keterlambatan bicara adalah salah satu penyebab gangguan perkembangan yang paling sering ditemukan pada anak. Keterlambatan bicara merupakan penyebab terbanyak pasien dikirim ke Unit Elektromedik. Tujuan: Untuk mengetahui profil hasil Brain Evoked Response Auditory (BERA) pada pasien anak dengan keterlambatan bicara di Klinik Elektromedik RSA UGM. Metode: Penelitian deskriptif observasional dengan menggunakan data sekunder. Pengambilan sampel dilakukan dengan teknik total sampling pada periode 1 Januari 2019 sampai dengan 31 Desember 2019. Responden yang memenuhi kriteria inklusi dan eksklusi berjumlah 86 anak. Sebagian besar responden berada pada rentang umur 2-<3 tahun (45,3%) dan berjenis kelamin laki-laki (68,6%). Hasil: Responden dengan hasil pemeriksaan BERA normal sejumlah 68 anak (79,1%), sedangkan sisanya sebanyak 18 anak (31,4%) tidak normal. Sebagian besar responden dengan hasil BERA normal berjenis kelamin laki-laki (42,6%), sedangkan pada responden dengan hasil BERA tidak normal, sebagian besar berjenis kelamin perempuan (66,7%). Responden dengan hasil BERA normal maupun tidak normal sebagian besar berada pada rentang umur 2-<3 tahun, masing-masing berjumlah 29 anak (42,6%) dan 10 anak (55,5%). Sebagian besar responden pada penelitian ini tergolong pada gangguan pendengaran berat (66,6%). Penelitian ini juga menunjukkan sebagian besar responden (77,8%) termasuk dalam jenis gangguan pendengaran Sensorineural Hearing Loss (SNHL). Kesimpulan: Responden dengan hasil BERA tidak normal ini menunjukkan sebagian besar (83,3%) mengalami gangguan pendengaran pada kedua sisi telinga (bilateral). Pasien anak dengan keterlambatan bicara yang dilakukan tes BERA sebagian besar hasilnya normal. Kebanyakan dari mereka berjenis kelamin laki-laki dan berusia 2-3 tahun.Kata kunci: Keterlambatan bicara, gangguan pendengaran, pemeriksaan pendengaran, Auditory Brainstem Response (ABR), Brain Evoked Response Auditory (BERA)